A travessia do trágico no romance d A Pedra do Reino de Ariano Suassuna - Magalhães, Yuri de Andrade (2013)
The present work seeks to investigate and discuss about the Greek Tragedy s elements at Ariano Suassuna s romance called τ Romance d A Pedra do Reino e o Principe do Sangue do Vai e Volta, connecting it directly to mythic, epic, poetic, and romances aspects at his work. The romance has as the protagonist the backcountry Pedro Dinis Quaderna. Quaderna is a character which is simultaneously popular, elitist, enigmatic, naive, and an intellectual man that has a great erudition. Quaderna is a character that seeks, by using the Literature, to reestablish a Brazilian backcountry kingdom which he s supposedly the king, always trying to empathizes the Brazilian northeast region like if it was a nation apart. By impressing a national personality to the Brazilian northeast , Quaderna tries to become an epic poet just like Homer, denoting a strong influence of the Epopee. Quaderna, just like many characters of Greek Tragedy, has at his family past time a lot of tragic circumstances. These facts that ocurred to his relativos like the your uncle Pedro Sebastião Garcia Barreto s death, the disappearement of his cousin Sinésio, and the contest between the brothers Arésio and Sinésio, and others aspects, remind us remarkable influences, beyond the Epopee, of the Greek Tragedy. By reading the romance we may notice many similarities between Quaderna s trajectory and Greek Tragedy heroes. To make an analysis about the tragic aspects at Suassuna s work, we need to dialogue with many theoreticals that have written about the tragic and comparate with many parts of Suassuna s with classics character s texts of Greek Tragedy. At the following chapters we seek to provide romance s elementaries notions, as well as tragic notions, the dialogue with mythics aspects and the tragic and epic aplicability at Suassuna s work